Hypoxia and Placental Development. Issue 17 (6th November 2017) - Soares, Michael J.; Iqbal, Khursheed; Kozai, Keisuke
Abstract : Hemochorial placentation is orchestrated through highly regulated temporal and spatial decisions governing the fate of trophoblast stem/progenitor cells. Trophoblast cell acquisition of specializations facilitating invasion and uterine spiral artery remodeling is a labile process, sensitive to the environment, and represents a process that is vulnerable to dysmorphogenesis in pathologic states. Hypoxia is a signal guiding placental development, and molecular mechanisms directing cellular adaptations to low oxygen tension are integral to trophoblast cell differentiation and placentation. Hypoxia can also be used as an experimental tool to investigate regulatory processes controlling hemochorial placentation. These developmental processes are conserved in mouse, rat, and human placentation. Consequently, elements of these developmental events can be modeled and hypotheses tested in trophoblast stem cells and in genetically manipulated rodents. Hypoxia is also a consequence of a failed placenta, yielding pathologies that can adversely affect maternal adjustments to pregnancy, fetal health, and susceptibility to adult disease. The capacity of the placenta for adaptation to environmental challenges highlights the importance of its plasticity in safeguarding a healthy pregnancy. Birth Defects Research 109:1309–1329, 2017.© 2017 Wiley Periodicals, Inc.